Risk Assessment in Developing KFX/IFX Fighter - Salsabiela, Bilqis Fitria; Midhio, I Wayan; Amperiawan, Gita (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2017)
This article is about the activity of risk assessment in developing KFX/IFX Fighters through joint development cooperation between Indonesia and South Korea for Engineering and Manufacturing Development Phase (EMDP). The Risks in EMDP found by using the Life Cycle of Weapon System. Risk assessment aims to identify, analyze and assess the level of risk as a calculation so that the program will always be on the track and the default of the project will be avoided. Moreover, this is the first experience for Indonesia to make fighters. Besides that, KFX/IFX fighters is one of our national program which aims to build the independence of defense industry and to open the road map in mastering on making fighter for PT. Dirgantara Indonesia (PT. DI).